An IT model of a Knowledge Map which supports management in small and medium-sized companies using selected Polish construction enterprises as an example - Hoła, Bożena; Sawicki, Marek; Skibniewski, Mirosław (Journal of Civil Engineering and Management, 2015)
Knowledge is one of the most important resources of an enterprise. Skillful knowledge management can bring significant benefits including labour productivity growth, an increase in quality of provided services and also a strengthening of the competitive position of an enterprise. This paper presents an IT model of a Knowledge Map which supports knowledge management in a construction enterprise. The model was developed on the basis of the results of surveys and analyses carried out in small and medium sized construction enterprises in Poland. The process approach in management was included in the proposed model and it involves analysis of an enterprise activity as a set of processes. The model contains processes occurring at enterprise level and also in the widely considered investment process in the construction industry. This assumption made the proposed Knowledge Map universal and able to be applied in construction enterprises operating in both the design and executive field.